Pharmacogenetic testing prior to carbamazepine treatment of epilepsy: patients' and physicians' preferences for testing and service delivery. (22nd August 2015) - Powell, Graham; Holmes, Emily A. F.; Plumpton, Catrin O.; Ring, Adele; Baker, Gus A.; Jacoby, Ann; Pirmohamed, Munir; Marson, Anthony G.; Hughes, Dyfrig A.
Abstract : Aim: Pharmacogenetic studies have identified the presence of the HLA‐A*31:01 allele as a predictor of cutaneous adverse drugs reactions (ADRs) to carbamazepine. This study aimed to ascertain the preferences of patients and clinicians to inform carbamazepine pharmacogenetic testing services. Methods: Attributes of importance to people with epilepsy and neurologists were identified through interviews and from published sources. Discrete choice experiments (DCEs) were conducted in 82 people with epilepsy and 83 neurologists. Random‐effects logit regression models were used to determine the importance of the attributes and direction of effect. Results: In the patient DCE, all attributes (seizure remission, reduction in seizure frequency, memory problems, skin rash and rare, severe ADRs) were significant. The estimated utility of testing was greater, at 0.52 (95% CI 0.19, 1.00) than not testing at 0.33 (95% CI –0.07, 0.81). In the physician DCE, cost, inclusion in the British National Formulary, coverage, negative predictive value (NPV) and positive predictive value (PPV) were significant. Marginal rates of substitution indicated that neurologists were willing to pay £5.87 for a 1 percentage point increase in NPV and £3.99 for a 1 percentage point increase in PPV. Conclusion: The inclusion of both patients' and clinicians' perspectives represents an important contribution to the understanding of preferences towards pharmacogenetic testing prior to initiating carbamazepine. Both groups identified different attributes but had generally consistent preferences. Patients' acceptance of a decrease in treatment benefit for a reduced chance of severe ADRs adds support for the implementation of HLA‐A*31:01 testing in routine practice.